Removal of Organic Dye Using Graphene-based Composite: Isotherm and Kinetic Studies - Preeti .; Meena Bhandari; Neeraj Kumari (Journal of Water and Environmental Nanotechnology)
In the present study, Graphene oxide (GO) and Graphene oxide-montmorillonite (GO-based Montmorillonite composites) composite was fabricated successfully and used further for the extraction of cationic pollutant, Malachite green (MG) oxalate. The structural characterization of synthesized composites was investigated through XRD, FT-IR, and FE-SEM techniques. Furthermore, GO and GO-based Montmorillonite composites are used as effective adsorbents in removing organic MG oxalate dye through batch extraction by varying pH, contact time, and concentration. XRD studies confirmed the successful formation of GO and exfoliated structure of GO-based Montmorillonite composites. The disappearance of peak at 2θ = 8.1° for GO-based Montmorillonite composites confirmed the homogenous distribution of GO sheets into layered Mt clay. The maximum uptake of Malachite green dye with GO-based Montmorillonite composites composite was 675 mg/g while in the case of GO, it was 315 mg/g. The more adsorption of dye in the case of GO-based Montmorillonite composites was due to the availability of additional functional groups resulting in more active site generation. The linear fitting of Langmuir isotherm and pseudo-second kinetic models further confirmed favorable chemical interaction of dye in the form of monolayer to both GO and GO-based Montmorillonite composites. Dye-adsorbed GO and GO-based Montmorillonite composites could be regenerated and used further for the adsorption of dye with more than 80% adsorption efficiency. Therefore, the study showed that GO-based Montmorillonite composites based Montmorillonite composites proved to be a promising and reasonably priced sorbent for the treatment of MG oxalate dye.